Koordinasi Pemerintah Desa Dalam Upaya Pemberdayaan Kelompok Tani Di Desa Bontomarannu Kabupaten Gowa - Apriliana, Nurul Hasmi; Fatmawati, Fatmawati; Nasrulhaq, Nasrulhaq (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study aimed to determine the Coordination of the Village Government in the Empowerment of Farmers Groups in Bontomarannu Village, Gowa Regency. This study used qualitative with 9 informants. Data collection techniques with in-depth interviews, direct observation, documentation. The results of this study showed that the communication carried out by the village government with effective farmer groups without strengthening the ego of each group was able to produce good coordination to support the forms of the empowerment process of farmers, village government and all farmer groups were very aware with the importance of coordination, all efforts in empowering farmers or farmer groups were more maximal, and coordination was very important between the village government and farmer groups that could produce forms of coordination such as maximum work results and also know all the needs of farmer groups in the field.